Design, construction and performance testing of a new system for energy saving in rural buildings - Khalaji Assadi , Morteza (ELSEVIER, 2011)
Drying fruit, heating residential buildings and providing a hot water supply in villages all consume energy. Using fossil fuel for these purposes creates pollution and costs too much. In contrast, the use of solar energy in these applications leads to a noticeable decrease both in pollution and investment costs. In this study, a new solar system was designed and tested in order to reduce energy usage in rural residential buildings and the food drying industry. As the peaks of energy consumption in the proposed system are not simultaneous, this new system is very effective in reducing energy consumption, controlling energy peaks and reducing environmental pollution. This system has the ability to provide the required energy in both summer and winter modes. In the summer mode, the energy supply is used for providing hot water and drying agricultural products, while in winter mode it is used for rural residences heating and hot water supply. Drying time has been varied between 51.23 and 42.45 h according to type of application, and average temperature difference between room and ambient is almost nearly 10 ◦C with different air heaters. The system includes energy supply and storage equipment, solar dryers, water collectors and rectangular, triangular, trapezoidal and double-pass with longitudinal fins air heaters. The system was tested in Iran for drying apricots, heating rural residential buildings and supplying hot water for domestic use, meanwhile, the energetic and exergetic efficiency of the system was calculated 37.3–61.3 and 3.2–9.7 respectively for different types of installations. © 2011 Elsevier B.V. All rights reserved